Trees and Me - Martha C. Monroe (EDIS)
The Forestry Trees and Me 4-H Project Book (4HFOM12) is the second in the series and for children ages 7–12. Each of the thirteen activities engage youngsters in exploring the interesting world of trees with exercises and thought questions. In Chapter 1, they will discover how trees grow. Chapter 2 includes strategies for identifying trees and 18 tree cards for the dominate species in 8 forest ecosystems across Florida. In Chapter 3, youth focus on the many benefits and values of trees, from wooden houses, rubber tires, and paper products, to restful and pleasing outdoor spaces.